Germinação e estabelecimento inicial de espécies congêneres de ambiente seco - Albuquerque, André Cardoso (2015)
In severe abiotic conditions, environmental filter selects phylogenetically related species. This trend promotes the problem of competitive exclusion, differentiation the regeneration niche for coexistence mechanism. There are studies of germination requirements and initial establishment of herbaceous species that indicate interspecific differences related to specialization pulse or interpulse, contributing to the coexistence in plant communities of arid and semi-arid environments. But there is a lack of studies seeking evidence for woody species. Seeking to fill the gap investigate differences in seed characteristics, germination and early development in two species of Mimosa. We found biometrics and water content in the seeds; germination under different temperatures; germination under different degrees of water stress; imbibition curve and initial development in lighting and irrigation treatments. Mimosa casealpiniifolia Benth. presented interpulse features on germination and early development, because of the higher seed size (larger amount of reserves); higher water content in the seed; Conservative soaking in water absorption curve; resistance to more intense water stress and better initial growth in water treatment interpulse than wrist. Mimosa tenuiflora Benth. showed characteristics of expertise to the wrists on germination and early development: small amount of reserves; low moisture content; rapid and greater water absorption in the imbibition curve; less resistance to water stress and better initial growth in pulse than interpulse. We conclude that the congeners studied tree species differ in the characteristics of seeds and germination; and have different initial responses and the development of treatments and interpulse pulse, so that indicates a performance difference in different moments of the water system; which can be related to the coexistence of these species.